The role of economics in cartel detection.A review of cartel screens - Zlatcu, Iuliana; Suciu, Marta-Christina (Journal of Economic Development, Environment and People, 2017)
. In their desire to gain market share and profit, companies often resort to certain anti-competitive practices. Among them, it is well known that cartels are considered the most serious infringement of competition law. Cartels aim to increase their prices and profits at the expense of the consumers’welfare by avoiding the risks of competition and reducing the uncertainty in the market. In order to uncover cartels, screens can be a useful tool for competition authorities, using them to support opening an investigation or to filter industries prone to anticompetitive behaviour for further investigation. Screens can also help authorities to estimate the duration of the infringement, by identifying the starting point and the ending of the respective practice. This paper reviews the main screens identified in the empirical literature and also used by competition authorities in order to uncover firms’ behaviours which are more likely to be consistent with collusion than with competition.